The double‐antigen ELISA concept for early detection of Erns‐specific classical swine fever virus antibodies and application as an accompanying test for differentiation of infected from marker vaccinated animals. Issue 6 (3rd February 2017) - Meyer, D.; Fritsche, S.; Luo, Y.; Engemann, C.; Blome, S.; Beyerbach, M.; Chang, C.‐Y.; Qiu, H.‐J.; Becher, P.; Postel, A.
Summary: Emergency vaccination with live marker vaccines represents a promising control strategy for future classical swine fever (CSF) outbreaks, and the first live marker vaccine is available in Europe. Successful implementation is dependent on a reliable accompanying diagnostic assay that allows differentiation of infected from vaccinated animals (DIVA). As induction of a protective immune response relies on virus‐neutralizing antibodies against E2 protein of CSF virus (CSFV), the most promising DIVA strategy is based on detection of E rns ‐specific antibodies in infected swine. The aim of this study was to develop and to evaluate a novel E rns ‐specific prototype ELISA ( pigtype CSFV E rns Ab), which may be used for CSF diagnosis including application as an accompanying discriminatory test for CSFV marker vaccines. The concept of a double‐antigen ELISA was shown to be a solid strategy to detect E rns ‐specific antibodies against CSFV isolates of different genotypes (sensitivity: 93.5%; specificity: 99.7%). Furthermore, detection of early seroconversion is advantageous compared with a frequently used CSFV E2 antibody ELISA. Clear differences in reactivity between sera taken from infected animals and animals vaccinated with various marker vaccines were observed. In combination with the marker vaccine CP7_E2alf, the novel ELISA represents a sensitivity of 90.2% and a specificity of 93.8%. However, cross‐reactivity with antibodies against ruminant pestiviruses was observed. Interestingly, the majority of samples tested false‐positive in other E rns ‐based antibody ELISAs were identified correctly by the novel prototype E rns ELISA and vice versa . In conclusion, the pigtype CSFV E rns Ab ELISA can contribute to an improvement in routine CSFV antibody screening, particularly for analysis of sera taken at an early time point after infection and is applicable as a DIVA assay. An additional E rns antibody assay is recommended for identification of false‐positive results in a pig herd immunized with the licensed CP7_E2alf marker vaccine.